Innovation and ambivalence: a narrative-dialogical perspective on therapeutic change - Gonçalves, Miguel M. (2018)
Change is indisputably one of the main goals of psychotherapeutic work. From a dialogical perspective, psychotherapeutic change entails a transformation in the transactional and communicative relationships established in the client’s “inner society of I-positions”. In the present chapter, we summarize the main findings of our narrative-dialogical research program on the processes of change in psychotherapy, privileging three related processes: the emergence of innovation, the occurrence of ambivalence (i.e., rejection of innovation), and 2 ambivalence resolution (i.e., back to innovation again). The systematic empirical study of these processes has been made possible by their operationalization and subsequent development of three process-oriented coding systems, respectively: the Innovative Moments Coding System, the Ambivalence Coding System, and the Ambivalence Resolution Coding System. Additionally, the theoretical and clinical implications of this empirical line of research is discussed and illustrated.